Third day in vitro-developed embryo cryopreservation. - Guzmán, Luis (2015)
Introduction: Freezing-unfreezing procedures are essential when hyperestimulation is followed by embryo overproduction; they lower costs and increase pregnancy rates per aspiration. Objectives: To present our experience with embryo freezing-unfreezing. Setting: Assisted Reproduction Medical Service and Laboratory, Clinica Ricardo Palma. Design: Clinical retrospective study. Biologic material: Embryos obtained by assisted fertilization. Interventions: Controlled ovarian hyperestimulation with short luteal phase, ova capture at 36 hours post hCG administration, classical in vitro fertilization or ICSI-transport, classical processes of embryo cryopreservation and unfreezing. Main outcome measures: Embryo survival in freezing-unfreezing process. Results: We started our study in October 2003. Number of cycles with frozen embryos during this period was 154; from these we unfroze only 58. Pregnancy rate per transference was 30,2%, obtaining 16 pregnancies, including 12 term pregnancies and 4 abortions. Conclusions: Results with embryo cryopreservation at our assisted reproduction service are consistent with those of other fertility centers.